A large-liver abscess with severe anaemia in 6 years-old patient: a case report - I Gusti Istri Agung Widnyani; I Putu Gede Karyana; I Gusti Ngurah Sanjaya Putra; Nyoman Metriani Nesa (DiscoverSys Inc., 2020)
Background: Liver abscess are infectious, space-occupying lesions in the liver; the two most common abscesses being pyogenic and amoebic. A pyogenic liver abscess (PLA) is a potentially lethal condition. This study aims to describe the signs, symptoms, and prognosis of pyogenic liver abscess in children with severe anaemia.Case Description: Six years old boy complained about abdominal pain for 4 months before admitted to the hospital. The abdomen began to stiff 23 days before. Since 4 weeks, there was several episodes of fevers, more than 4 times but not more than 3 days, relieved by antipyretic. Every fever followed by a stomachache. His parents said he looked paler than before and his activities decreased, was sleepy and irritable. In physical examination, we found the patient looked anaemic, with a distended abdomen with hepatomegaly. Routine CBC revealed: WBC was 16.99, Hemoglobin was 5.45g/dL platelet was 796.20, iron parameters was: iron serum: 11.27 ug/dL (normal: 50-120 ug/dL) TIBC: 180 ug/dL(normal 225-450 ug/dL). A liver abscess 4.5 cm x 5.1 cm with liquefaction was obtained by ultrasound and confirmed by abdomen MSCT with contrast 4,4 x 4,3 x 6,1 cm. The patient family refused abscess draining surgery, so only conservative therapy by antibiotics was given and further followed up in polyclinic. Nine-month after therapy, follow up by ultrasound was normal.Conclusion: The sign and symptom of pyogenic LA were non-specific; abdomen MSCT confirmed the diagnosis with contrast. The prognosis was good.